High-dose bolus injection of urokinase: use during cardiopulmonary resuscitation for massive pulmonary embolism - Böttiger, Bernd W.; Reim, Stefan M.; Diezel, Gabriele; Böhrer, Hubert; Martin, Eike (Chest, 1994)
Bolus administration of high-dose thrombolytic agents has been reported for the treatment of acute pulmonary embolism. We describe the case of a 60-year-old woman who suffered a massive pulmonary embolism with cardiopulmonary arrest 21 h after an exploratory laparotomy. After 20 min of unsuccessful cardiopulmonary resuscitation (CPR), a bolus of 2,000,000 U of urokinase was injected via a peripheral vein. Ten minutes later, the circulatory system stabilized, and the patient survived without subsequent bleeding. In our opinion, bolus lysis made a definitive contribution to the success of the resuscitation. Several other case reports and small series showed successful treatment of pulmonary embolism during similar circumstances using high-dose bolus injection of thrombolytic agents. Mechanical thrombus fragmentation using a pulmonary artery catheter or pulmonary embolectomy has not been shown to be more successful during resuscitation. We conclude that bolus administration of thrombolytic agents during CPR for massive pulmonary thromboembolism may be an acceptable and successful technique, which also is available even in the community hospital setting.
Elektronische Reproduktion der Druck-Ausgabe 15. Januar 2016
Gesehen am 08.05.2024